INFLUENCE OF LAND RELIEF (TERRAIN) ON SOIL MOISTURE REGIME AND PRODUCTIVITY OF SPRING WHEAT AND BARLEY - R. R. Abdulvaleev; V. B. Trots (Зерновое хозяйство России, 2018)
While cultivating crops on sloping lands it’s necessary to know the level of land relief influence on plant productivity. The purpose of research is to study the effects of different types of slopes on distribution of snow, water reserves in soil and productivity of spring soft wheat and barley. The trials were carried during 2012-2014 years on the lands of SBEI “Aksenovsky Agricultural Technical School”, located on the southern part of Bugulmino-Beleevskaya Hill. The research focused on the north-east, east, south-east, southern and western slopes. The soil of the slopes is leached chernozem (blacksoil). The trials showed that on any sloping lands the greatest amount of snow gathered in the lower part of the slope. It allows accumulating about 11,6-194,3 mm of atmospheric moisture and storing 157-211 mm of water in the upper soil layer (0-0,7m), which is on 35,3-43,3% more than in the upper part of Bugulmino-Beleevskaya Hill. If we plant spring soft wheat in the lower part of the Hill, we’ll obtain the yield of 1,84 – 2,12 t/ha of wheat and 1,80 – 2,27 t/ha of barley. It’s in average on 3,4-29,6% more than the productivity of crops planted in the middle part of the hill and in 1,2-2,1 times more than the productivity of the crops planted in the upper part of the slopes. It’s more appropriate to plant spring wheat on the western slopes and barley on the south-east and northern slopes, if you want to obtain maximum yield of them.